Some Aspects of a Dialogue with Dostoevsky - Beržaitė, Dagnė (Respectus Philologicus, 2006)
This article deals with problems of intertextuality concerning two different literary texts created in absolutely different times and countries: the famous Russian writer F. Dostoevsky’s story "The Eternal Husband" (1870) and the contemporary American writer lrving’s novel "World According to Garp" (1978). M. Bakhtin wrote that Dostoevsky’s word causes and influences the next and another one; according to J. Kristeva and M. Jones, one text as a system cannot be understood without the knowledge of the previous systems. The article is trying to prove that Dostoevsky’s text of "The Eternal Husband" not only evidently influences lrving’s novel but also transforms its narrative and ideological structure; also that lrving uses the Russian writer’s text as a leitmotiv to his own text.